Molecular Characteristics of Multidrug Resistant Acinetobacter baumannii Isolated from Baghdad Hospitals - K. AL-Masoudi, Khitam; M. AL-Saffar, Jinan; J. Kendla, Nuha (Iraqi Journal of Science, 2023)
A total of 100 clinical sample from (urine, sputum and swabs of wound , burn and ear) were collected from patients in different hospitals of Baghdad during the period from December 2013 to May 2014. 15 isolates (15%) identified belong to Acinetobacter baumannii, swabs of wounds were represented in high percentage of A.baumannii isolates (40%) while percentage of other samples were variable. Susceptibility of 15 A.baumannii isolates were tested toward 16 different Antimicrobial agents, the results showed all isolates were multi drug resistant. In addition, Polymerase Chain Reaction Technique (PCR) was performed to detection the resistance genes encoding the Oxacillinases enzymes. The PCR analysis showed that the presence of insertion sequence (ISAba1) in 13 isolates whereas blaoxa51like gene was represented in 12 isolates. Furthermore, the results of detection other genes were not appear any amplification for all A.baumannii isolates with genes encoded for bla oxa 58 and bla oxa 143 enzyme.